Sistem Pengelolaan Data Karyawan Secara Online di PT. DARMA HENWA, Tbk-ACP - Setiawati, Erlina; Dede Prahma, Wisudawan (Journal Information Technology Trends (JITRENDS), 2024)
The employee data collection system is an important part of employee management in the company. The information system required for the storage and management of employee information by PT Darma Henwa Tbk-ACP, a mining company in Asam-asam. In addition, this study also wants to find out the use of data collection information systems for employees at PT Darma Henwa Tbk-ACP and how this can affect operational efficiency and personnel management